Helping students develop listening comprehension (2000)
Listening practice is often neglected or handled inappropriately in the teachinglearning process. This poses problem because listening is an integral part of conversations. Oral skills without equally welldeveloped listening abilities are of little practical value. In this article, I will take a look at issues related to the area of listening that may be considered when guiding students toward developing listening comprehension.